PROCESS CAPABILITY IMPROVEMENT IN PUMPING ELEMENT MANUFACTURING - Chandrachood.B, Dr.Divakar.H.N Nandini.T.S, Devaraju.G.R (International Journal of Research Science and Management, 2015)
In modern automotive industries, specifications for products have been continuously improved due to performance competition. Pumping element is an important component of a Diesel fuel injection system this project was carried out in Bosch Ltd. Utilizing Process capability, Pareto analysis, cause and effect diagram and Histogram to improve the nature of manufacturing procedure of Plunger, Barrel and Elements. Optimization strategy is presented to enhance the performance of the process in concurrent engineering environment. Value Stream Mapping (VSM) tool helps in identifying critical time lag factors in process functioning is a major deterrent in process efficiency. This work focuses on Process capability improvement in VSM.